Intermediate accounting 2 - Millan, Zeus Vernon B. (Baguio City : Bandolin Enterprise, 2021)
This book is based on current Philippine Financial Reporting Standards (PFRSs).
1. Business combinations (part 1) -- 2. Business combinations (part 2) -- 3. Business combinations (part 3) -- 4. Consolidated financial statements (part 1) -- 5. Consolidated financial statements (part 2) -- 6. Consolidated financial statements (part 3) -- 7. Consolidated financial statements (part 4) -- 8. Separate financial statements -- 9. Financial reporting in hyperinflationary economies -- 10. The effects of changes in foreign exchange rates -- 11. Accounting for derivatives and hedging transactions (part 1) -- 12. Accounting for derivatives and hedging transactions (part 2) -- 13. Accounting for derivatives and hedging transactions (part 3) -- 14. Accounting for derivatives and hedging transactions (part 4) -- References.
Includes bibliographical references.
Keywords: ACCOUNTING